The complete mitochondrial DNA of the tropical gar (Atractosteus tropicus). (2nd January 2016) - Del Río-Portilla, Miguel A.; Vargas-Peralta, Carmen E.; Lafarga-De La Cruz, Fabiola; Arias-Rodriguez, Lenin; Delgado-Vega, Rigoberto; Galván-Tirado, Carolina; García-de-León, Francisco J.
Abstract: The mitogenome of the tropical gar, Atractosteus tropicus, (GeneBank accession number KJ531198) has a total length of 16, 280 bp, and the arrangement consist of 13 protein-coding genes, 2 ribosomal RNA (rRNA) genes and 22 transfer RNA similar to other Lepisosteidae family mitogenomes.